1994
DOI: 10.1080/15428119491018330
|View full text |Cite
|
Sign up to set email alerts
|

Workers' Exposure to Airborne Bacteria and Endotoxins at Industrial Wastewater Treatment Plants

Abstract: A study of sewage workers' exposure to airborne culturable bacteria and inhaled endotoxins was performed at nine waste-water treatment plants that treat mainly industrial effluents. Airborne endotoxins were collected on glass fiber filters and analyzed using a chromogenic limulus assay. Endotoxin concentrations measured in the immediate vicinity of the waste-water treatment process varied from 0.1 to 350 ng/m3. The eight-hour time weighted average concentrations of endotoxin to which workers were exposed excee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 0 publications
3
35
0
Order By: Relevance
“…These results agree well with the other reports, especially with the data published by Laitinen et al (1994) who found that most of the bacteria-carrying particles in the air of a WWTP had an aerodynamic diameter below 4.7 lm. It is interesting to note that the patterns of the size distributions of airborne fungi are generally very similar to bacterial size distributions but have the peaks, typically, in the size range between 2.1-3.3 and 3.3-4.7 lm.…”
Section: Resultssupporting
confidence: 83%
“…These results agree well with the other reports, especially with the data published by Laitinen et al (1994) who found that most of the bacteria-carrying particles in the air of a WWTP had an aerodynamic diameter below 4.7 lm. It is interesting to note that the patterns of the size distributions of airborne fungi are generally very similar to bacterial size distributions but have the peaks, typically, in the size range between 2.1-3.3 and 3.3-4.7 lm.…”
Section: Resultssupporting
confidence: 83%
“…Wastewater, especially hospital wastewater, contains a variety of potentially pathogenic microorganisms (Laitinen et al, 1994;Pillai et al, 1996;Tsai et al, 1998). Particles containing bacteria can be aerosolized from the bubbling surface during the aeration process in wastewater treatment plants (WWTP) (Ulevicius et al, 1997), which increases the risk of communicable infections and other health effects associated with wastewater treatment to sewage workers and the public.…”
Section: Introductionmentioning
confidence: 99%
“…For a detailed interpretation of the findings for TPT and OPT in the context of occupational exposure it would be necessary to carry out measurements of the concentrations of air pollutants in each workplace, which could be the subject of further studies. There are literature reports on the studies concerning air concentrations of harmful biological and chemical agents in the sewage treatment plant and landfill areas [5,18,[22][23]. Studies investigating the correlation between exposure to hydrogen sulphide and endotoxins and the illnesses diagnosed among sewage and landfill workers were conducted by Ray [23], Abdou [24] and Lee [19].…”
Section: Taste and Smell Perception Among Sewage Workers O R I G I N mentioning
confidence: 99%
“…As regards the biological agents, an increased concentration of bacteria, fungi, viruses, protozoans, microorganisms, and organic dusts, including among others endotoxins and glucans, has been observed in both workplaces [4][5][6][7][8][9]. The specific character of work in the municipal waste and water treatment plant is connected with workers' exposure to irritants, sensitizing agents, toxicants and other substances which often have an unpleasant odour.…”
Section: Introductionmentioning
confidence: 99%